2019
DOI: 10.3390/atmos10020071
|View full text |Cite
|
Sign up to set email alerts
|

An Expanded Investigation of Atmospheric Rivers in the Southern Appalachian Mountains and Their Connection to Landslides

Abstract: Previous examination of rain gauge observations over a five-year period at high elevations within a river basin of the southern Appalachian Mountains showed that half of the extreme (upper 2.5%) rainfall events were associated with an atmospheric river (AR). Of these extreme events having an AR association, over 73% were linked to a societal hazard at downstream locations in eastern Tennessee and western North Carolina. Our analysis in this study was expanded to investigate AR effects in the southern Appalachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
0
19
0
1
Order By: Relevance
“…Similarly, the relief at SHW is only 54 m and imparts no orographic effect. Rainstorms vary throughout the year in both study locations and tend to be more convective in the summer and more frontal in the winter (Laseter, Ford, Vose, & Swift, 2012; Miller, Miniat, Wooten, & Barros, 2019). At CHL, spatial patterns of rainfall are reinforced more strongly by elevation during the summer months (Daly, Slater, Roberti, Laseter, & Swift, 2017), likely due to convective storms generating over higher elevations.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the relief at SHW is only 54 m and imparts no orographic effect. Rainstorms vary throughout the year in both study locations and tend to be more convective in the summer and more frontal in the winter (Laseter, Ford, Vose, & Swift, 2012; Miller, Miniat, Wooten, & Barros, 2019). At CHL, spatial patterns of rainfall are reinforced more strongly by elevation during the summer months (Daly, Slater, Roberti, Laseter, & Swift, 2017), likely due to convective storms generating over higher elevations.…”
Section: Methodsmentioning
confidence: 99%
“…Inland ARs have been linked to heavier precipitation and flooding in the central U.S. (Lavers & Villarini, 2013; Nayak et al., 2016) and landslides in the Appalachian Mountains (Miller et al. 2019). In this work, we extend these previous analyses of inland AR impacts to the Upper Great Lakes region, located in the northern mid‐latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a 22-yr study in California showed that 60–90% of shallow landslides coincide with atmospheric rivers (Oakley et al, 2018). Landslides are also important hazards in other mountainous areas; thus, the AR-landslide relationship has begun to be investigated in other regions, including the Southeast U.S. (Miller et al, 2019).…”
Section: Ar Impacts On Landscapes and Water Resourcesmentioning
confidence: 99%